Is there an association between thyroid dysfunction and breast cancer? - Maira Mahmood Bokhari, Rukhshan Khurshid, Uzma Jabbar, Faiza Aamir, Aamenah Malik, Huma Sattar, Arif Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The association between thyroid disease and breast cancer risk remains unclear. A cross-sectional study was carried out to find the association between hypothyroidism, hyperthyroidism, and breast cancer. Materials and Methods: The study included 71 diagnosed cases of breast cancer patients belonging to stage III of the disease. The mean age of controls and patients was 43-45 years. Their level of thyroid hormones was estimated. On the bases of high and low levels of thyroid hormone, women were divided into group one (hypothyroidism n= 56) and group two (hyperthyroidism n=15). Levels of neutrophils, lymphocytes, and hematocrit were estimated by the SWISS MAX analyzer. The level of thyroid hormones, TSH, 8OHG, Isoprostane, and 4-HNE was estimated by the technique of ELISA. The level of MDA was estimated spectrophotometrically. Results: It was observed that body weight was high in hypothyroid females (group 1) Levels of neutrophils, lymphocytes, and monocytes were significantly higher in group 1 of the breast cancer afflicted women, as compared to the controls and group 2. The level of thyroid hormones FT3, FT4, and TSH was also higher in group 1. The level of MDA, isoprostane, and 4-HNE was significantly high in both women with hypo and hyperthyroidism as compared to controls. Conclusions: We found an increased risk of breast cancer in women with hyporhyroidism and a slightly decreased risk in women with hyperthyroidism indicating an association between thyroid function level and breast cancer risk.